2000
DOI: 10.1021/jp000291y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Li-Doped MgO Catalysts for Oxidative Coupling of Methane by Means of Mg K-Edge XANES

Abstract: To characterize active defect sites in the near-surface and bulk phase of MgO in Li-doped MgO, structural analyses were carried out by means of XRD, XPS, Mg K-edge XANES, and SEM techniques. For Li-MgO calcined at 873 K, Li doping at a low content (2.5 wt % as Li) brings about the formation of defect species only in the near-surface, which is due to the localization of doped Li ions in the surface. In this case, the catalytic species containing a Li + -Ocenter exists in the surface region. At higher contents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 43 publications
7
22
0
Order By: Relevance
“…It has been claimed, even with the smaller Li + ions, that oxygen defects prevail in the near-surface and not in the bulk phase. 40,41 We, therefore, propose that the K + / Na + are located at the surface and not in the "bulk" of the MgAlO x . Our tentative mechanism is that K + plus substitutes a Mg 2+ , and additional oxygen vacancies at the surface are created.…”
Section: Resultsmentioning
confidence: 92%
“…It has been claimed, even with the smaller Li + ions, that oxygen defects prevail in the near-surface and not in the bulk phase. 40,41 We, therefore, propose that the K + / Na + are located at the surface and not in the "bulk" of the MgAlO x . Our tentative mechanism is that K + plus substitutes a Mg 2+ , and additional oxygen vacancies at the surface are created.…”
Section: Resultsmentioning
confidence: 92%
“…Differences in the relative intensities of A, B and C were attributed by Wong et al (1994) to variations in the number of coordinating OH ligands in various materials. In brucite (Mg(OH) 2 ) for example, where Mg2 + is octahedrally coordinated by OH groups, octahedra share adjacent edges to form layer structures, giving a XANES spectrum (Yoshida et al 1995;Aritani et al 2000) very similar to enstatite. Although silicates also contain Si-O tetrahedra with H, O or OH at their vertices the similarity of the XANES for brucite and enstatite suggests silicate Mg K-edge XANES features are due to the existence of a larger structure containing ordered octahedral Mg extending well beyond the first coordination shell.…”
Section: Mg K-edge Xanesmentioning
confidence: 99%
“…37 As well as studies of catalytic activity, [38][39][40][41][42][43] fundamental studies have been focused on effects of Li dopants on the electronic, optical, and magnetic properties of MgO. [44][45][46][47][48][49][50] In the recent density-functional theory ͑DFT͒ study by Scanlon et al, 50 doping of Li in the top layer of MgO͑100͒ was shown to create an unoccupied state with O 2p valence character which assists catalytic hydrogen abstraction.…”
Section: Introductionmentioning
confidence: 99%